Determining the Relationship between Severity of Clinical Symptoms and Severity of Radiographic Findings in Patients with Knee Osteoarthritis - Maysa Ghayyem; Shahab Shafeian; SainaAmintoosi; Behdad Nadimi; Mohsen Ghorbani; Saeid Gholami Emam Moghadam; Sina Faghani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This study was conducted to determine the relationship between severity of clinical symptoms and severity of radiographic findings in patients with knee osteoarthritis.Methods: In this cross-sectional analysis, 84 patients with knee osteoarthritis were studied. Clinical signs, including pain, joint effusion, morning stiffness, and limb deformity, were compared with the Kellgren and Lawrence radiographic classification reviewed by each patient.The relationship between K/L garde and BMI, age, duration of disease and gender was also investigated.Results: This study conducted on 84 patients with knee osteoarthritis found a significant direct relationship betweenquantitative pain, VAS, and K/Lscore,as well asqualitative pain and K/L score(P=0.000).Moreover, there was a significant relationship between morning stiffness duration and gender (P=0.012). A direct relationship was also reported between disease duration and K/L score of patients (P=0.000) and Pearson coefficient was positive.Conclusion: this study proved that with increasing VAS and patients’ pain, patients are in a higher classification of K/L score.